2022
DOI: 10.4103/1673-5374.314294
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte pathology in fetal alcohol spectrum disorders

Abstract: The pathology of fetal alcohol syndrome and the less severe fetal alcohol spectrum disorders includes brain dysmyelination. Recent studies have shed light on the molecular mechanisms underlying these white matter abnormalities. Rodent models of fetal alcohol syndrome and human studies have shown suppressed oligodendrocyte differentiation and apoptosis of oligodendrocyte precursor cells. Ethanol exposure led to reduced expression of myelin basic protein and delayed myelin basic protein expression in rat and mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…To explore one potential structural mechanism that could contribute to VEP latencies in development (independent of PAE), we also tested associations in a subsample of infants with an MRI-derived estimate of myelin, the T1w/T2w ratio. PAE has been shown repeatedly to impact myelination (Darbinian & Selzer, 2022; Donald et al, 2015; Ghazi Sherbaf et al, 2019; McLachlan et al, 2019; Newville et al, 2017, 2022; Wozniak & Muetzel, 2011). Moreover, while it is largely accepted that the significant accumulation of myelin in the brain at least partially explains the shortening of VEP latencies across infancy, as far as we are aware, this is the first empirical study to test the relation between cortical myelination and VEP latencies in infancy (though one prior study found decreased subcortical myelination, indexed by diffusion tensor imaging, was linked to longer P1 VEP latencies; Dubois et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To explore one potential structural mechanism that could contribute to VEP latencies in development (independent of PAE), we also tested associations in a subsample of infants with an MRI-derived estimate of myelin, the T1w/T2w ratio. PAE has been shown repeatedly to impact myelination (Darbinian & Selzer, 2022; Donald et al, 2015; Ghazi Sherbaf et al, 2019; McLachlan et al, 2019; Newville et al, 2017, 2022; Wozniak & Muetzel, 2011). Moreover, while it is largely accepted that the significant accumulation of myelin in the brain at least partially explains the shortening of VEP latencies across infancy, as far as we are aware, this is the first empirical study to test the relation between cortical myelination and VEP latencies in infancy (though one prior study found decreased subcortical myelination, indexed by diffusion tensor imaging, was linked to longer P1 VEP latencies; Dubois et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Animal model literature and human literature beginning in childhood have characterized the effects of alcohol exposure on myelination (e.g., Almeida et al, 2020; Darbinian & Selzer, 2022; Milbocker et al, 2022). Human histological studies also provide evidence for the impact of PAE on dysmyelination (Darbinian & Selzer, 2022).…”
Section: Contextualizing Pae In South African Communitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Alcohol is a teratogen that can easily cross the placenta, disrupting the fetus’ neurodevelopment at any stage. Disruptions include, but are not limited to, altered neuronal proliferation and migration (Almeida et al, 2020; Veazey et al, 2013), synaptogenesis (Adams et al, 2023; Basavarajappa & Subbanna, 2023), dendritic spine morphology (Cui et al, 2010; Lee et al, 2021), and gliogenesis and myelination (Cantacorps et al, 2017; Darbinian & Selzer, 2022), including phospholipid metabolism (Darbinian et al, 2023; Hwang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%